The Analysis of Unsignalized Intersection Road Performance at Manukan Wetan Surabaya City - Muhan Fahri Irzadi; Sri Wiwoho Mudjanarko; Ikhsan Setiawan; Joewono Prasetijo; Hary Moetriono (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2020)
Surabaya is the capital of the province of East Java and is the second largest city in Indonesia after Jakarta. As a city that will continue to develop, the mobility of the people is getting higher, as well as the progress of the current means of transportation which is increasing, causing traffic problems, one of which occurs at intersections. One of the intersections that will be reviewed is the Raya Manukan intersection. This study uses the MKJI 1997 guideline, with primary data collection by means of traffic conditions survey and secondary collection, namely data on the number of vehicle growth from the Department of Population and Civil Registry of Surabaya City. This study aims to determine the performance of the unsigned intersection at the Raya Manukan intersection. With this research data, as well as from the results of traffic analysis at the Raya Manukan intersection with the boundary from the Amd Street Intersection to the Buntaran Street Intersection. From the calculation results, it is obtained that the intersection capacity is 3750.9 pcu / hour, with a degree of saturation value of 0.8254. From the results of the analysis, the calculations that have been carried out have not been able to reach the desired degree of saturation value, which is as suggested by MKJI 1997.Therefore then an alternative is made with road widening engineering and produces a saturation degree value of 0.7493, so that the road widening on Raya Manukan Kulon is the best alternative in solving the capacity problem of Intersection Manukan.